Eremitis linearifolia and E. robusta (Poaceae, Bambusoideae, Olyreae): two new species of herbaceous bamboos from Brazil first collected over 30 years ago - Ferreira, Fabrício Moreira; Hollowell, Victoria C.; Oliveira, Reyjane P. (Phytotaxa, 2016)
Two new species of the herbaceous bamboos genus Eremitis are described and illustrated under the names Eremitis linearifolia and E. robusta. They occur in small populations in the Atlantic Rain Forest vegetation, from the states of Espírito Santo and Bahia, Brazil, respectively. Both species are known from only two sites. Both new species were first collected in the early 1980s. We discuss the morphological characters distinguishing these new species from their close relatives, and provide an identification key to all described species of Eremitis.